Business Resilience and Social Inclusion: A Critical Reflection on Internal Marketing - Contreras, Francia; Alvarado, Tania Elena Gonzalez (Mercados y Negocios, 2021)
The aim of the paper is to identify the dimensions of the Internal Marketing that contributes to business resilience and social inclusion. Marketing is approached as a tool for social transformation. The documentary and data analysis focused on the relevant theoretical and practical models proposed in the last decades. It concludes with the proposal of four dimensions of internal marketing that stimulate business resilience and social inclusion wich are: 1) the attraction and development of talent through the competitiveness of the workplace; 2) organizational change; 3) leadership development and empowerment; and 4) communication for the exchange of knowledge and motivation.